1995
DOI: 10.1111/j.2042-3306.1995.tb04958.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the oestrous cycle on electrolyte excretion in the mare

Abstract: Summary Equine rhabdomyolysis syndrome (ERS) has been reported to occur more frequently around oestrus. Because electrolyte imbalances have been implicated in pathogenesis, this preliminary study was designed to investigate the possible influence of concentrations of reproductive hormones, progesterone and oestradiol‐17β upon the 24 h%FE values of certain electrolytes. Over a 35 day period, daily plasma progesterone concentrations were measured in 4 mature Thoroughbred mares and serum oestradiol‐17β concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Nerveless, in the mare this trend results controversy. Two previous studies in mares by Kinslow et al [ 21 ] and Collins et al [ 55 ] showed large increases in the volumetric urinary excretion of Na + in samples collected during the period from 2 days preceding to 4 days following estrus, compared to the rest of the cycle. Positive correlations between P4 and Na + , K + and C1 − and between E2 and C1 − suggested that ovarian steroid hormones may exert an influence on urinary excretion of electrolytes in the mare.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nerveless, in the mare this trend results controversy. Two previous studies in mares by Kinslow et al [ 21 ] and Collins et al [ 55 ] showed large increases in the volumetric urinary excretion of Na + in samples collected during the period from 2 days preceding to 4 days following estrus, compared to the rest of the cycle. Positive correlations between P4 and Na + , K + and C1 − and between E2 and C1 − suggested that ovarian steroid hormones may exert an influence on urinary excretion of electrolytes in the mare.…”
Section: Discussionmentioning
confidence: 98%
“…In mares, Kinslow et al [ 21 ] showed large increases in the urinary excretion of Na + in samples during the period from day −2 to + 4 days of estrus, compared to the rest of the cycle. P4 is generally considered to be a “Na + —losing” steroid or an “ALD antagonist” [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Variation in excretion of electrolytes over a 24 h period has been reported (Morris et al 1984) and food intake can obviously affect values. Twenty-four hour volumetric excretion of electrolytes can vary with the oestrous cycle and among individuals (Kinslow et al 1995). Monthly evaluation of urinary fractional excretion of phosphate and sodium showed no correlation with predisposition to rhabdomyolysis ).…”
Section: Electrolytesmentioning
confidence: 93%